Green House Gas Emission Inventory and Energy Use Of TPS3R Flamboyan Using Waste Reduction Model (WARM) V.15 - Asrining Ghina Maulidia; Filson Maratur Sidjabat; Temmy Wikaningrum (Journal of Environmental Engineering and Waste Management, 2023)
Abstract. Emissions are the result of human activities that increase the concentration of greenhouse gas gases such as CCl2F2, CO2, N2O, and  CH₄, Increasing the attention of the gases above will increase the greenhouse effect which ultimately increases the earth's temperature. The existence of a waste management site can produce greenhouse gas emissions from vehicle transportation, composting processes, TPA to recycling. One of the roles of Flamboyan's TPS3R is to reduce the amount of plastic waste by recycling and composting and the residue will go to Cipeucang TPA for landfilling. This is an effort to reduce the amount of organic and non-organic waste, but the recycling, and composting. Landfilling processes can produce CO2 in the waste processing and distribution process, so it is necessary to calculate the amount of CO2 from the baseline management of municipal solid waste that will be compared with alternative municipal solid waste scenarios to see the conclusion of the analysis using the Waste Reduction Model (WARM) application. Objectives: The objective of this journal is to calculate the greenhouse gas emission and energy use of TPS3R Flamboyan. Method: The secondary data was obtained from TPS3R Flamboyan’s management. The writer use description analysis. Result: 1.     the inventory calculation result of GHG emission current condition and alternative condition are -5,24 and -6,5. 2.   Total energy use in the current condition is -58,79 and the alternative condition with HDPE recycling is -92,68 Conclusion: 1. the inventory calculation result of GHG emission current condition and alternative condition are -5,24 and -6,5. 2. Total energy Use in the current condition is -58,79 and the alternative condition with HDPE recycling is -92,68.